Penerapan Konsep Usaha dan Energi Dalam Persfektif Sains dan Al-Qur’an - Hadi, Su (Universitas PGRI Palembang, 2022)
The purpose of this study was to determine the application of the concept of effort and energy in the perspective of science and the Qur'an. The type of research used is library research, which is a series of activities related to library data collection methods. In this study, the authors use sources from the Qur'an, interpretations, books, articles and from other sites related to the research. The results of the research conducted that the effort in the perspective of science is the product of the force and displacement. Meanwhile, in the perspective of the Qur'an, effort is discussed in Qs. An-Najm verse 39. The energy used as an example is the kinetic energy of mountain movement. According to the perspective of science, kinetic energy is the energy possessed by objects because they have speed, so when the mountain moves, it means the mountain has kinetic energy. Meanwhile, in the perspective of the Qur'an, kinetic energy is discussed in Qs. An-Naml verse 88